The technical infrastructure for Remote Participation in the European Fusion Programme - How, John; Schmidt, Volker (Fusion engineering and design, 2002)
Remote Participation in European Fusion Research has now undergone a period of practical application with the C1–C4 Campaigns in the EFDA-JET Scientific Programme in 2000 and 2001. We report on the Technical Infrastructure established at a European level in the JET framework for the support of this type of approach. We present the five technical poles of the RP project: Remote Data Access, Remote Computer Access, Network Connectivity, Telecommunications, and Support/Documentation. Many of these subjects are covered in more depth in other papers at this conference. In each topic we describe the current state, but go on to address future progress, difficulties and open questions. We make recommendations for the future technical requirements, with a goal of a well established, closely bound “Virtual Fusion Association” for a combined European strategy, including the JET EP project, inter-Association collaborations, and the ITER project, in which physical location of scientific effort and support staff is expected to become less important than it is today.